Advancement of the Aging Process of the Population in Poland between 1990 and 2050 - Murkowski , Radosław (Studia Oeconomica Posnaniensia, 2018)
The aging of a population means that there is an increase in the proportion of elderly people in the population, which is a consequence in the changes in the scope of their mortality and fertility. Currently, people are considered as being in their old age when they reach the age of 60 or 65. However, nowadays a person at the age of 60 is definitely not in a similar health condition as a person aged 60 a hundred years ago. Therefore, it is vital how we define the beginning of old age. In addition, from the point of view of the aging of a given population, it is not important to only reach a certain age considered as the beginning of old age, but the crucial point is how long is the lifespan after reaching it. Therefore, the main goal of the paper is the assessment of the extent of the aging of the population in Poland in the years 1990-2050. This should be done by using not only traditional measures, but also potential and alternative measures.